Rethinking Islamic Pedagogy for Diversity: A Conceptual Analysis of Moderate Islamic Education's Role in Reducing Prejudice in Multicultural Social Settings - Masdar Hilmy; Moh. Dannur; Nur Syarifuddin (Jurnal Studi Pendidikan Agama Islam, 2026)
This conceptual study aims to develop a theoretical framework examining how moderate Islamic pedagogy can reduce prejudice within multicultural societies. Through systematic library research analyzing 127 sources including peer-reviewed journal articles, scholarly books, and policy documents, this study identifies four primary pedagogical mechanisms synthesized into the "Moderate Islamic Pedagogy for Prejudice Reduction" (MIPPR) model. The findings demonstrate that embodied pedagogy teachers' enactment of moderation values through daily actions constitutes the most dominant mechanism (38.2% of studies supporting), surpassing the influence of formal curriculum. Sacred texts possess a dual role: becoming sources of inclusivity when taught through contextual-reinterpretive approaches, yet reinforcing exclusivist prejudice when taught through literal-decontextual approaches. Classroom ecology providing optimal contact conditions (equal status, cooperation, institutional support) significantly moderates moderate education's positive effects on prejudice reduction. Teacher identity particularly reflective awareness of personal biases serves as a crucial mediating variable between training and student learning outcomes. The MIPPR model offers an empirically testable framework with practical implications for curriculum development, teacher training, and classroom ecology design in Islamic schools. This study contributes to integrating Islamic education theory, social psychology, and multicultural pedagogy.